A short history of financial euphoria: financial genius before the fall - Galbraith, John Kenneth ([Knoxville, Tenn.] : Whittle Direct Books, 1990)
Can the lessons of history help us to avoid financial calamity? How can the investor be saved from the consequences of financial euphoria, from flights of mass insanity?
Includes bibliographical references (p. 84-85).
osc 25/9/17
Loans
Keywords: Speculation